Utilizing rGH + Spirulina in Fish Feed to Enhance The Growth and Pigmentation of Betta Fish (Betta, spp.) - Nursanti Abdullah; Eko S Wibowo; Rovina Andriani (Journal of Global Sustainable Agriculture, 2023)
This study aims to evaluate the effect of the addition of growth hormone (rGH) and spirulina flour on the performance of absolute weight growth, survival, feed efficiency, and feed conversion ratio (FCR) of cupang fish (Betta spp.). This study used a completely randomized design (CRD) with four treatments with three replications, i.e., A) Dose of growth hormone 1.5 mg+3 g spirulina flour; B) Dose of growth hormone 2 mg+3g spirulina flour; C) Dose of growth hormone 2.5+3 g spirulina flour; D) Control (no treatment). The results showed that the addition of growth hormone (rGH) and spirulina to commercial feed affected absolute weight growth of 2.27 ± 0.90 g. The survival rate was 75.00±1.11 %, the feed efficiency value was 28.98±1.17 %, and the feed conversion ratio was 1.11±0.022. The highest color intensity was found in treatment C with a score of 6.